Rule-Based Machine Translation: An Interface between Formal and Natural Language Syntax A Violation of Case Filter Principle (2016)
The principles which govern ways words can be combined together to form phrases and sentences in natural language is known as syntax while formal syntax is not a matter of experience (unlike natural language), but stipulations in order to provide a specified set of strings in a computer programming language. The focus of this paper therefore, is to explore linguistics as the dual planes of theory and practice, by interrogating how PROLOG was used to capture English/Yoruba natural language syntax in a rule-based machine translation. The study reveals that the machine was able to generate sentences, break sentences into phrases and words in a bid to translate them in both languages